Respostas

2014-02-22T10:26:57-03:00
X² - 3x - 4 = 0 ~> a = 1 , b = -3 , c = -4

Δ = b² - 4ac
Δ = (-3)² - 4.1.(-4)
Δ = 9 - (-16)
Δ = 25

x = -b ± √Δ
         2a

x = -(-3) ± √25 
           2.1

x = ± 5
        2

x' = 3 + 5 = 8 = 4                x" = 3 - 5 = -2 = -1
         2       2                               2       2

S = { -1 , 4 }
3 5 3
2014-02-22T10:27:30-03:00
X² - 3x -4 =

a- 1
b- -3
c- -4

Δ = b² - 4ac
Δ = (-3)² - 4 (1)(-4)
Δ = 9 + 16 = 25

x = -b +- √Δ
         2a
x = -(-3) +- √25
          2(1)
x= 3 +- 5
        2
x¹ = 3 + 5 = 8 = 4
         2        2
x² = 3 - 5 = -2 = -1
          2      2
2 3 2